ANALYZING CODE-SWITCHING AND CODE-MIXING USED BY JERRY BAYNARD AND DIANA BARRY IN THE TV SERIES ANNE WITH AN E - Adhinianti, Zalfaa Fikriyya; Wulandari, Dwi (English Literature Study Program, Faculty of Humanities, Diponegoro University, 2025)
This article focuses on analyzing code-switching and code-mixing in English-French-speaking characters utilized by Jerry Baynard and Diana Barry. Jerry and Diana acquired different second languages and they have different backgrounds. Jerry's second language is English and he comes from a lower class family. Meanwhile, Diana's second language is French and she comes from a wealthy and well-mannered family. A descriptive qualitative method is used to explain the phenomenon of code-switching and code-mixing used by Jerry Baynard and Diana Barry in the TV series Anne with an E. The researcher used theory from Wardhaugh (1986), Muysken (2000), and Holmes (2001: 41). According to the findings there are two types of code-switching found and one type of code-mixing found. Most of the data was influenced by function factor.